THE CORRELATION OF TRANSAMINASES AND LIVER DISEASES - Bastianus Alfian Juatmadja; I Wayan Putu Sutirta Yasa; DAP Rasmika dewi; Bagus Komang Satriyasa (Faculty of Medicine, Udayana University, 2013)
The symptoms of liver diseases are very diverging, from the mild one till the severe one. Sometimes we may find that severe heart disorders but the symptoms are too less. We need some tools to make a good diagnosis. We can not only use a good anamnesis, but also have to use good physical examination and the other support test. Transaminase also called aminotransferase. This aminotransferase catalyzes the transfer of the amino group (?NH2) of an amino acid to a carbonyl compound. The liver contains specific transaminases for the transfer of an amino group from glutamic acid to ?-keto acids that correspond to most of the other amino acids. Other transaminases catalyze reactions in which an amino group is transferred from glutamic acid to other compounds. Transamination is one of the principal mechanisms for the formation of necessary amino acids in the metabolism of proteins. Transaminase as a sign to cell damage may divided into Serum Glutamic Oxalocetic Transaminase (SGOT), Serum Glutamic Pyruvic Transaminase (SGPT), and Lactic Dehydrogenase (LDH). Gamma GT and alkali fosfatase correlate with cholestasis. Cholinestrase correlate with liver synthesis capacity.